2000
DOI: 10.1161/01.hyp.35.6.1215
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Natriuretic Peptide Is Involved in Renal Actions of Moxonidine

Abstract: Abstract-Moxonidine, an antihypertensive imidazoline compound, reduces blood pressure by selective activation of central imidazoline I 1 -receptors and inhibition of sympathetic nerve activity and by direct actions on the kidney, with both mechanisms resulting in diuresis and natriuresis. We hypothesized that the hypotensive and renal actions of moxonidine may be mediated by atrial natriuretic peptide (ANP), a cardiac peptide involved in pressure and volume homeostasis through its vasodilatory, diuretic, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…One month treatment with moxonidine did not significantly affect blood pressure. These findings fully agree with the reported inability of moxonidine and other centrally acting drugs to produce hypotension, particularly in presence of low or normal blood pressure (Motz et al 1998; Mukaddam-Daher and Gutkowska 2000). It is imperative to note that, even in the absence of hypotension, centrally acting drugs cause significant suppression in cardiac sympathetic activity (Mobini et al 2006;Van Kerckhoven et al 2000).…”
Section: Discussionsupporting
confidence: 86%
“…One month treatment with moxonidine did not significantly affect blood pressure. These findings fully agree with the reported inability of moxonidine and other centrally acting drugs to produce hypotension, particularly in presence of low or normal blood pressure (Motz et al 1998; Mukaddam-Daher and Gutkowska 2000). It is imperative to note that, even in the absence of hypotension, centrally acting drugs cause significant suppression in cardiac sympathetic activity (Mobini et al 2006;Van Kerckhoven et al 2000).…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have suggested that the decrease in plasma AVP plays a partial role in the profound diuretic effect of xylazine through its action on  2 -adrenoceptors [3, 10, 11 17, 18]. In our recent study [16], we suggested that ANP might partially influence xylazine-induced diuresis in dogs because it exerts a diuretic and natriuretic action on the renal proximal tubules and inner medullary duct cells of the kidney in rats [12,13]. The regulation of water excretion has implications for a number of clinical situations.…”
mentioning
confidence: 71%
“…However, the level of ANP stimulated by atipamezole at the tested doses is not considered to be enough to induce diuresis. Stimulation of plasma ANP release has been reported to be related to the atrial stretch due to hypertension [8,12,13]. Atipamezole produces stronger and relatively longer hypertension [4,8,20].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have recently identified I 1 -receptors in heart atria and ventricles and shown that atrial I 1 -receptors are up-regulated in rat hypertension and ventricular I 1 -receptors are up-regulated in human and hamster heart failure (El-Ayoubi et al, 2002a). In other studies, we demonstrated that acute injections of moxonidine, an imidazoline compound that shows 40 times higher affinity to I 1 -receptor versus ␣ 2 -adrenoceptors, are associated with enhanced release of atrial natriuretic peptide (Mukaddam-Daher and Gutkowska, 2000), a cardiac hormone involved in pressure and volume homeostasis. Together, these studies led us to suggest that heart I 1 -receptors are functional and may be involved in cardiovascular regulation.…”
mentioning
confidence: 72%